Assessment of Public Pharmaceutical Supply Management System at Rural Primary Health Centers in Udupi District, Karnataka - Balakrishnan Kokilam, Monica; Ganesh Joshi, Harish; Ganesh Kamath, Veena (Indian Journal of Pharmacy Practice)
In India, Karnataka is more urbanized and is supported with an extensive healthcare system assisted with welltrained qualified personnel. In the year 2002, Karnataka Drugs Logistics and Warehousing Society were launched to supply free drugs to all health facilities under government administration. The existing system has proved advantageous over the previous system that was functioning under Government Medical Stores. Aim: The objective of this study is to assess the public pharmaceutical procurement and distribution system that is followed at the rural primary health centers in Udupi district, Karnataka; processes followed to achieve accessibility to essential drugs. Methods: Retrospective data was collected during the period 2012-13 to 2014-15 from a cross-sectional study conducted in Udupi district, Karnataka. The collected data is related to the supply system adopted for public procurement and distribution of essential pharmaceuticals in the district to ensure accessibility and availability of essential medicines. The data was collected from a set of sampled primary health centers located in the rural area across Udupi district. Results and Discussion:An explosive increase in population, demographic changes, higher incidence, and prevalence of diseases has contributed to a steep growth in health care expenditure and level of complexity. In order to match the increasing demand rate, tremendous developments in the field of public health care have been achieved over the decades to provide “good health” to all. However, the system facades a lot of defies in the pharmaceutical segment dealing with drug selection, usage, regulations, uninterrupted access (physically and financially), availability, affordability, information flow, data standardization and coordination between the main players and activities in the system. A holistic approach in drug management is not addressed effectively in the state and thus leading to incongruous usage of pharmaceuticals in the public healthcare sector. Conclusion: Overall, it can be observed that there are several areas that can improved within the public pharmaceutical supply system to improve the accessibility to essential drugs at the primary healthcare level. Incorporation of standardized strategic methodology with Information and Communication Technology interventions in processes dealing with pharmaceutical purchasing, selection, quantification, distribution, management of human resource, and inventory management will drive the system towards achieving “Good Health to all.”
Keywords: KDLWS; Public rural healthcare; Pharmaceutical procurement in Karnataka; Public drug supply and distribution in Udupi; Primary health centers (rural)